Appling the analytic hierarchy process as the risk evaluation model to improve hospital biomedical waste disposal outsourcing quality - Chao-Chung Ho; Ming-Shu Chen (International Journal of Management, Economics and Social Sciences (IJMESS), 2017)
Improvement of medical quality has become a trend in hospital development. In recent years, environmental protection has become a rising issue in Taiwan, and people have begun to discuss the biomedical waste that comes from hospitals. According to an estimate in "To Err is Human," published by Institute of Medicine, the economic loss resulting from medical malpractice is about 17 to 29 billion, and the question of whether biomedical waste is properly disposed of is included as an incident of medical malpractice. Therefore, this study aimed to study use risk evaluation in order to screen out evaluation factors. Subsequently, the Analytic Hierarchy Process was employed to determine the weight of each factor. The results of the study provide hospitals with biomedical outsourcing critical risk factor criteria and their order by importance and can be provided to hospitals as reference for the management of biomedical waste disposal outsourcing.
Keywords: 330; Analytic Hierarchy Process (AHP); biomedical waste; waste management; outsource; medical wastes